Primary School Children’s Ideas about ‘Plants’ and Use of Constructivist Approach - Singhal, mamta (JOURNAL OF INDIAN EDUCATION, 2021)
Children come to the class with their own ideas about the natural phenomenon. Even before getting a formal exposure of learning scientific concepts, they have experienced them in their daily life. Their experiences and interactions about natural phenomenon are often unplanned and transcend into the domains of science, social science, psychology and culture. They form their own understanding about the world which interferes with their learning of scientific concepts in the school. Children’s prior ideas are given different names such as pre-conceptions, misconceptions, alternative frameworks, etc., in different researches. Irrespective of the nature of these ideas, the most important step is to explore and acknowledge these ideas. This paper is based on the research conducted with primary school children studying in government schools of Delhi. The study explored children’s ideas about plants using qualitative research tools and addressed them using constructivist approach.